Between-person and within-person associations of sleep and working-memory in the everyday lives of old and very old adults: initial level, learning, and variability - Lücke, Anna J.; Wrzus, Cornelia; Gerstorf, Denis; Kunzmann, Ute; Katzorreck, Martin; Schmiedek, Florian; Hoppmann, Christiane; Schilling, Oliver (Sleep, 2022)
Sleep duration affects various aspects of cognitive performance, such as working-memory and learning, among children and adults. However, it remains open, whether similar or even stronger associations exist in old and very old age when changes in sleep and cognitive decrements are common.Using repeated daily-life assessments from a sample of 121 young-old (66-69 years old) and 39 old-old adults (84-90 years old), we assessed links between sleep duration and different aspects of working-memory (initial level, practice-related learning, and residualized variability) between and within persons. Participants reported their sleep durations every morning and performed a numerical working-memory updating task six times a day for seven consecutive days.Both people who slept longer and those who slept shorter than the sample average showed lower initial performance levels, but a stronger increase of WM over time (i.e. larger learning effects), relative to people with average sleep. Sleep duration did not predict performance variability. Within-person associations were found for people sleeping relatively little on average: For them, working-memory performance was lower on days with shorter than average sleep, yet higher on days with longer than average sleep. Except for lower initial levels of working-memory in old-old adults, no differences between young-old and old-old adults were observed.We conclude that sufficient sleep remains important for working-memory performance in older adults and that it is relevant to include different aspects of working-memory performance, because effects differed for initial performance and learning.